Przynależność pokoleniowa jako explanandum zmian mentalności społecznej w okresie przeobrażeń systemowych = Generation affiliation as the explanandum of changes in social mentality in the period of political transformations - Zielińska, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main aim of the article is the attempt at answering the question whether and to what extent current changes and differences of opinion of the youngest generations of the Poles in chosen analytic areas (i.e., in the field of political attitudes, moral values and social conventions) are indicative of permanent changes in mentality, and to what extent they can be the basis for predicting the future character of society.
Keywords: mentalność społeczna; pokolenie; zmiany pokoleniowe; postawa społeczna; normy obyczajowe; wartości moralne